Correlation Analysis of Lignin Accumulation and Expression of Key Genes Involved in Lignin Biosynthesis of Ramie (Boehmeria nivea) - Tang, Yinghong (Genes (Basel), 2019)
The phloem of the stem of ramie (Boehmeria nivea) is an important source of natural fiber for the textile industry. However, the lignin content in the phloem affects the quality of ramie phloem fiber. In this study, the lignin content and related key gene expression levels were analyzed in the phloem and xylem at different developmental periods. The results showed that the relative expression levels of lignin synthesis-related key genes in the xylem and phloem of the stem gradually decreased from the fast-growing period to the late maturation period, but the corresponding lignin content increased significantly. However, the relative expression levels of a few genes were the highest during the maturation period. During all three periods, the lignin content in ramie stems was positively correlated with the expression of genes, including PAL, C4H and 4CL1 in the phenylpropanoid pathway, F5H and CCoAOMT in the lignin-specific synthetic pathway, and CAD in the downstream pathway of lignin synthesis, but the lignin content was negatively correlated with the expression of genes including 4CL3 in the phenylpropanoid pathway and UDP-GT in the shunt pathway of lignin monomer synthesis. The ramie 4CL3 recombinant protein prefers cinnamic acid as a substrate during catalysis, and it negatively regulates lignin synthesis. It is speculated that ramie 4CL3 is mainly involved in the synthesis of ramie flavonoid compounds, and that 4CL1 is mainly involved in lignin synthesis.